2021
DOI: 10.1007/s00134-021-06389-z
|View full text |Cite
|
Sign up to set email alerts
|

Natural history, trajectory, and management of mechanically ventilated COVID-19 patients in the United Kingdom

Abstract: Purpose The trajectory of mechanically ventilated patients with coronavirus disease 2019 (COVID-19) is essential for clinical decisions, yet the focus so far has been on admission characteristics without consideration of the dynamic course of the disease in the context of applied therapeutic interventions. Methods We included adult patients undergoing invasive mechanical ventilation (IMV) within 48 h of intensive care unit (ICU) admission with complete clinical data unt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 36 publications
4
41
2
Order By: Relevance
“…The prevalence of persistent severe ARDS seems similar to non-COVID ARDS [ 11 ] (or even non-COVID acute hypoxemic respiratory failure) [ 25 ] and so is the mortality. This is also in line with findings of a recent observational study from the United Kingdom, which reported that refractory hypoxemia remains a major determinant of mortality in the COVID-19 era [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of persistent severe ARDS seems similar to non-COVID ARDS [ 11 ] (or even non-COVID acute hypoxemic respiratory failure) [ 25 ] and so is the mortality. This is also in line with findings of a recent observational study from the United Kingdom, which reported that refractory hypoxemia remains a major determinant of mortality in the COVID-19 era [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…While trajectory-related subphenotypes (namely, rapidly improving ARDS and persistent severe ARDS) have been characterized in the pre-COVID era [ 4 , 5 , 11 ], little is known about the trajectory of ARDS in patients with COVID-19. Given that the trajectory of COVID-related ARDS is increasingly recognized as more clinically relevant than a single daily value of oxygenation [ 14 , 15 ], we endeavoured to determine the prevalence and prognosis of rapidly improving ARDS and of persistent severe ARDS among intubated patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no difference between the compared groups (vitamin C vs. control) in terms of known predictors of mortality in COVID-19 (and therefore potential confounders), such as age, sex, comorbidities, SOFA score and lung mechanics at baseline (35). If anything, baseline oxygenation of mechanically ventilated patients was worse in the vitamin C than control group (PaO 2 :FiO 2 95.4 vs. 142.5), which could attenuate a potentially beneficial effect of vitamin C on mortality.…”
Section: Discussionmentioning
confidence: 88%
“…Health systems across Europe were overwhelmed by the first coronavirus disease 2019 (COVID-19) wave [ 1 3 ]. While initially media and governments focused on shortages of ventilators, devices, and drugs [ 4 , 5 ], the European Society of Intensive Care Medicine (ESICM) leadership immediately focused the attention on intensive care unit (ICU) teams and competencies of healthcare workers in case of ICU surges [ 6 , 7 ].…”
mentioning
confidence: 99%